SMARTPHONE ADDICTION AND ITS IMPACT ON SLEEP HEALTH AND PRODUCTIVITY OF HEALTH STUDENTS - Raule, Jean Henry (Journal of Public Health Indonesian, 2025)
Smartphone addiction in college students—especially health students—correlates with sleep disturbances and decreased academic productivity. This study aims to analyze the relationship between smartphone addiction (SA), sleep quality, and productivity in health students and test the mediating role of sleep quality. The research design uses a cross-sectional quantitative approach with purposive sampling. Instruments include the Smartphone Addiction Scale–Short Version (SAS-SV) for SA and the Pittsburgh Sleep Quality Index (PSQI) for sleep quality; Productivity is measured through GPA indicators, late assignment collection, and self-rated academic productivity indexes. Statistical analysis includes multiple regression and bootstrapped mediation. The results showed that SA was positively associated with poor sleep quality and negatively associated with productivity. Sleep quality mediates in part the influence of SA on productivity. The findings confirm the importance of sleep hygiene interventions and the regulation of smartphone use in the health campus environment. This study contributes by focusing on the health student population in Indonesia and testing a measured sleep quality mediation model with validated instruments.